2015
DOI: 10.1021/acsnano.5b03318
|View full text |Cite
|
Sign up to set email alerts
|

Quantized Conduction and High Mobility in Selectively Grown InxGa1–xAs Nanowires

Abstract: We report measured quantized conductance and quasi-ballistic transport in selectively regrown In0.85Ga0.15As nanowires. Very low parasitic resistances obtained by regrowth techniques allow us to probe the near-intrinsic electrical properties, and we observe several quantized conductance steps at 10 K. We extract a mean free path of 180 ± 40 nm and an effective electron mobility of 3300 ± 300 cm(2)/V·s, both at room temperature, which are among the largest reported values for nanowires of similar dimensions. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 30 publications
2
31
0
Order By: Relevance
“…Furthermore, it was shown that these transistors operate in the quasi-ballistic regime with a transmission of about 70 %, which was obtained from quantized conductance measurements at 10 K, and was shown to be valid also at room temperature [5]. Here, we performed 1/f and RTS noise measurements on devices with varying gate lengths (Lg = 50-85 nm) and gate widths (W = 27-100 nm).…”
Section: Methods and Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…Furthermore, it was shown that these transistors operate in the quasi-ballistic regime with a transmission of about 70 %, which was obtained from quantized conductance measurements at 10 K, and was shown to be valid also at room temperature [5]. Here, we performed 1/f and RTS noise measurements on devices with varying gate lengths (Lg = 50-85 nm) and gate widths (W = 27-100 nm).…”
Section: Methods and Resultsmentioning
confidence: 79%
“…The In0.85Ga0.15As NWs are formed on semi-insulating InP:Fe by selective area MOCVD growth using HSQ as a growth mask [5]. Each device consists of a single nanowire.…”
Section: Device Fabricationmentioning
confidence: 99%
“…Each device consists of a single NW. The composition of the NW is In 0.85 Ga 0.15 As, as determined by optical characterization [15]. Fig.…”
Section: Device Fabricationmentioning
confidence: 99%
“…high electron mobility µ e and long mean free path λ [6]. While the relatively low DOS of indium-rich In x Ga 1-x As is predicted to limit I DS in highly scaled devices, compared to competing technologies such as Si and Ge, this may be offset by the gain from the long λ and high µ e of In x Ga 1-x As [15]. Since this technology likely will be implemented in a 3D channel architecture, such as FinFETs or NWFETs, a further question concerns the dependence of λ on the channel dimensions, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation